(untitled) (Circe de clásicos y modernos, 2018)
The treatise De mundo develops a surprising synthesis of the philosophical thought in Roman Imperial times in seven chapters. The presentation of the philosophy as the supreme science is followed by the interpretations of the natural order according to the five elements and by the explanation of the harmony of gods’ heaven and men’s earth, plus a description of the geography and the meteorology of the world as the home of the supreme god, who governs the State as a cos-mic king. Although there are scholars who still attribute the treatise’s authorship to Aristotle, this translator claims that the writing of the text could not have been done earlier than the first century BC, cf. Méthexis 11, 1998, 103-111.